2021
DOI: 10.1101/2021.02.02.429458
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Naive human B cells engage the receptor binding domain of SARS-CoV-2, variants of concern, and related sarbecoviruses

Abstract: Exposure to a pathogen elicits an adaptive immune response aimed to control and eradicate. This initial exposure is imprinted on the immune system, so that a subsequent encounter to the same pathogen or a variant will result in a memory recall response that is often protective. Interrogating the naive B cell repertoire in terms of both abundance and specificity to said pathogen may contribute to an understanding of how to potentially elicit protective responses. Here, we isolated naive B cells across 8 human d… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 137 publications
(182 reference statements)
1
12
0
Order By: Relevance
“…1C). The reactivity to the RBD antigen observed in most of the acute outpatients with COVID-19 indicate activation of the humoral response and is suggestive of the development of neutralizing antibodies with the capacity to block SARS-COV-2 spike protein interaction with its cognate receptor ACE-2 as previously reported [17, 20]. The presence of viral RNA without serological response suggests false-positive PCR or atypical antibody responses, which have been reported in some patients [17, 21].…”
Section: Discusionsupporting
confidence: 65%
“…1C). The reactivity to the RBD antigen observed in most of the acute outpatients with COVID-19 indicate activation of the humoral response and is suggestive of the development of neutralizing antibodies with the capacity to block SARS-COV-2 spike protein interaction with its cognate receptor ACE-2 as previously reported [17, 20]. The presence of viral RNA without serological response suggests false-positive PCR or atypical antibody responses, which have been reported in some patients [17, 21].…”
Section: Discusionsupporting
confidence: 65%
“…Recently, through the analysis of human naïve B cells, some naïve antibodies have been shown to bind to the receptor-binding domain of SARS-CoV-2 and can neutralize SARS-CoV-2 pseudoviruses even in the absence of somatic mutations (11,12). Furthermore, although the clinical settings are different from our study, kidney transplant recipients and dialysis patients have diminished humoral responses to BNT162b2 with reduced B cells (13).…”
Section: Main Textmentioning
confidence: 53%
“…CoV-2 ACE2 receptor binding domain (RBD), albeit weakly, and may be engaged upon vaccine exposure to generate germinal centers and then follow affinity maturation process [48,49]. Indeed, Rincon-Arevalo et al observed a significant difference in the frequency of SARS-CoV-2 RBD-specific naïve B cells between BNT162b2-responders and nonresponders [50].…”
Section: Discussionmentioning
confidence: 99%